Establishment of assessment and decision criteria in human health risk assessment for substances with endocrine disrupting properties under the EU plant protection product regulation (Berlin, 2010)
"Chemical substances with a potential to modulate the hormonal system may have harmful effects on human or animal health, if they are included in plant protection products. Consequently, the new EU plant protection regulation (EC) No 1107/2009 names as one of the cut-off criteria that an active substance, safener or synergist shall only be approved if it is not considered to have endocrine disrupting properties that may cause adverse effects in humans, unless the exposure of humans under realistic proposed conditions of use is negligible. However, the new regulation fails to provide measures concerning specific scientific criteria for the assessment and decision on substances with endocrine disrupting properties. Specific criteria are to be presented by the European Commission within four years. To address this need, the German Federal Institute for Risk Assessment (BfR) hosted an expert workshop to establish assessment and decision criteria in human health risk assessment for substances with potential endocrine disrupting properties. It was strongly recommended by a majority of workshop participants to replace the preliminary interim criteria implemented in the regulation (EC) No 1107/2009 in the decision making process by specific scientific criteria at the earliest time possible. Prior to the workshop, a conceptual framework for evaluating potentially adverse endocrine effects and their relevance for humans under realistically proposed exposure conditions was presented by the BfR. Central aspects considered and discussed within this conceptual framework for a tiered decision process included the analysis of adversity of effects on the endocrine system, of mechanistic data to establish a mode or mechanism of action in animals, and of relevance of such effects to humans. The proposal was modified and considered useful as a starting point for the development of measures to be adopted in accordance with the regulatory procedure."